Occupational skin diseases - Diepgen, Thomas L. (Journal der Deutschen Dermatologischen Gesellschaft, 2012)
Occupational skin diseases are the most commonly reported notifiable occupational diseases. In Germany, 23 596 out of a total of 71 263 reported occupational diseases in 2010 were classified as occupational skin diseases (BK No. 5101: “severe or recurrent skin diseases which have forced the person to discontinue all occupational activities that caused or could cause the development, worsening, or recurrence of the disease”). Contact dermatitis (allergic, irritant) of the hands is the most common skin disease and atopic skin diathesis is often an important co-factor. The number of work-related skin diseases is many times higher than the number of notified occupational dermatoses. This CME article explains the legal framework of occupational diseases, the tasks and obligations of the legal statutory work insurance. Typical allergens and irritants of high risk professions are also presented as are the important steps from diagnosis to compensation. Early prevention of occupational skin diseases is very important to avoid severe chronic hand eczema. Therefore the “dermatologist's report” is crucial. Other occupational dermatoses (outside of BK 5101) are briefly mentioned. In recent years the number of notifications of occupational skin cancer due to occupational UV-irradiation has increased. According to recent epidemiological findings, there is a significant and consistent positive association between occupational UV-irradiation and squamous cell carcinoma. Therefore, an important criterion for a new occupational disease is fulfilled.